2012
DOI: 10.1371/journal.pone.0027885
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Firms: Constraints to Growth among Private Health Sector Facilities in Ghana and Kenya

Abstract: BackgroundHealth outcomes in developing countries continue to lag the developed world, and many countries are not on target to meet the Millennium Development Goals. The private health sector provides much of the care in many developing countries (e.g., approximately 50 percent in Sub-Saharan Africa), but private providers are often poorly integrated into the health system. Efforts to improve health systems performance will need to include the private sector and increase its contributions to national health go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Moreover, a study in Nepal by Devkota et al 18 drew a similar conclusion, where they found that approximately 18% of women who had intended to deliver at a health facility ended up delivering at home. These findings are in agreement with Kenya's KDHS that showed that most of the health facilities are over 5km radius from the consumers of services 19 .…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, a study in Nepal by Devkota et al 18 drew a similar conclusion, where they found that approximately 18% of women who had intended to deliver at a health facility ended up delivering at home. These findings are in agreement with Kenya's KDHS that showed that most of the health facilities are over 5km radius from the consumers of services 19 .…”
Section: Discussionsupporting
confidence: 91%
“…The decrease in the provision of healthcare services during the strike period could drive the public towards private healthcare system. However, most Ghanaians cannot afford the services of private healthcare facilities owing to the relatively high cost of treatment [20]. These individuals are left with the option of waiting on the news of resumption of work by nurses and midwives so that they can access healthcare.…”
Section: Plos Onementioning
confidence: 99%
“…The country has in the recent past introduced the National Health Insurance Scheme (NHIS) that seeks to extend basic medical care to the general public after registration and payment of premiums [11]. There are also other private health insurance providers associated with different firms and organizations in the country [12,13]. Despite government's efforts to extend healthcare to the greater percentage of the people in the country, the system is ridden with so many problems that frustrate healthcare seekers in time of need [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The demographic data of the participants included age, gender, marital status, level of education, religion, place of work, years or duration of work and place of residence. Twelve (12) participants were successfully interviewed (1 male and 11 females). The age range of the participants was 26 years to 40 years; six (6) of them attained tertiary (bachelor's degree) education and the other 6 had diploma in Psychiatric Nursing.…”
Section: Demographic Characteristicsmentioning
confidence: 99%